The Nominal Address Terms Found In The Movie Harry Potter And The Chamber Of Secrets As English Teaching Material - Kurnia Utami, Putu; Mas Indrawati, Ni Luh Ketut (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 27 No 1 (2020): Maret, 2020)
This study aims to analyze the types of nominal address term and the factors which influenced the choice of it found in the movie Harry Potter and the Chamber of Secrets as well as how to use them as authentic teaching material in English class. This study used the movie Harry Potter and the Chamber of Secrets as the data source. The method of collecting data are, first, the movie was watched. Second, the script of the movie was downloaded from the internet. Then, the script was read. While reading the script, the address terms found were noted. Furthermore, if there were a lot of potential data found to be used, the data were selected into particular ones that were relevant to support the analysis. Once the data were collected, they were classified by the types. The factors constraining the polite choice of address terms then were analyzed. Based on the analysis, there are several types of nominal address terms found in the movie such as name terms, occupational term, title, kinship term and term of endearment. There were three types of name terms found in the object of the study, they are first name, family name and full name. The factors that influenced the choice of address terms are the intimacy between the addresser and the addressee, the social relationship, and the setting of the conversation. The movie can be used as an authentic material to be used in English class to exposed students to the real language and give the appropriate context about when to use the language.